Brown coal humic substances hybrid modified biodegradable composites wear simulation - Lebedev, Vladimir Vladimirovich; Miroshnichenko, Denis Viktorovich; Tykhomyrova, Tetyana Sergiivna; Kochetov, Mykyta Sergiyovich ("Interdruk" Poland, Warszawa, 2023)
Researching on wares modeling from brown coal humic substances hybrid modified biodegradable composites based on polylactide and coffee waste technology are carried out in this work. New wares are pots for seedlings and vases for planting greenery that can be used for landscaping for urban territories. The products design was made, the mathematical modeling of the designed products was carried out. The process of modeling products based on brown coal humic substances hybrid modified biodegradable composites based on polylactide and coffee was carried out in the SolidWorks 2020: 3D CAD environment with subsequent receipt of g-code, which is intended for machines for the production of molds for plastic injection.
Keywords: modeling; humic substances; brown coal; biodegradable; composite; polylactide; coffee waste; wares